Correlates of Lifetime Physical Abuse Among Schoolchildren Aged 15 Years in Post-communist Albania - Qirjako, Gentiana; Dika, Qamil; Mone, Iris; Draçini, Xheladin; Kuneshka, Loreta; Roshi, Enver; Burazeri, Genc (Frontiers in Public Health, 2021)
Aim: Our aim was to assess the prevalence and correlates of lifetime physical abuse among schoolchildren in Albania, a post-communist country in South Eastern Europe which is currently undergoing a rapid socioeconomic transition. Methods: The third wave of Health Behavior in School-Aged Children (HBSC) in Albania was conducted in 2017-18 including a nationwide representative sample of 1708 schoolchildren aged 15 years (54% girls; response rate: 95%). Children were asked to report on lifetime physical abuse and a wide range of socio-demographic factors, lifestyle factors and health status characteristics. Binary logistic regression was used to assess the independent association of lifetime physical abuse with covariates. Results: Overall, the prevalence of lifetime physical abuse was about 32% (30% in boys vs. 32% in girls). In multivariable-adjusted logistic regression models, independent positive correlates of lifetime physical abuse among Albanian schoolchildren included lifetime smoking (OR=1.5, 95%CI=1.1-2.2), lifetime alcohol consumption (OR=1.6, 95%CI=1.2-2.1), irritability (OR[daily vs. rarely/never]=2.0, 95%CI=1.3-3.0), and especially lifetime witnessed domestic violence (OR=4.2, 95%CI=2.2-7.9). Conversely, a higher score on life satisfaction was inversely related to lifetime physical abuse (P<0.01). Conclusion: Our study provides novel evidence about the magnitude and selected independent correlates of lifetime physical abuse among schoolchildren in Albania, a country still embedded in an everlasting transition which is associated with tremendous changes in family structure, community links and societal norms and values. Irrespective of a wide range of sociodemographic factors and health characteristics, lifetime smoking, alcohol consumption, irritability, a lower score on life satisfaction and, particularly, witnessed domestic violence were strong and significant correlates of lifetime physical abuse among Albanian schoolchildren aged 15 years. Policymakers and decision-makers in Albania and elsewhere should be aware of the negative impact of child abuse and implement prompt and effective programs for control and prevention of all forms of child maltreatment.